2017
DOI: 10.1016/j.sdentj.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism, pattern of third molar and mandibular second premolar agenesis in Indian paediatric orthodontic patients

Abstract: Agenesis of third molars was more commonly seen in the maxilla, having male predilection. Maxillary right third molar was the most commonly missing tooth irrespective of gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
1
3
2
4
Order By: Relevance
“…Contrary to the findings from our study, in the studies of Mishra et al ( 18 ), Kaur et al ( 19 ) and Upadhyaya et al ( 20 ), M3 agenesis was found more frequently in males. The female predilection was similar to that reported by Sandhu and Kaur ( 21 ) and Sujon et al ( 16 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to the findings from our study, in the studies of Mishra et al ( 18 ), Kaur et al ( 19 ) and Upadhyaya et al ( 20 ), M3 agenesis was found more frequently in males. The female predilection was similar to that reported by Sandhu and Kaur ( 21 ) and Sujon et al ( 16 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Celikoglu et al ( 27) and Mishra et al (18) reported that the missing of all M3 teeth was more frequently found than the presence of M3 teeth, similar to the findings of this study. In the study of Mishra et al (18), upper right M3 agenesis had the highest prevalence while lower left M3 agenesis had the lowest prevalence. But, in this study, lower right M3 agenesis had the highest prevalence.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations